Data Privacy Assessment: An Exemplary Case for Higher Education Institutions - Ali Habbabeh; Bettina Schneider; Petra Maria Asprion (International School for Social and Business Studies, 2019)
The European General Data Protection Regulation (GDPR), which became applicable in May 2018, obliges companies and thus Higher Education Institutions (HEIs) to (re)assess their data privacy procedures, in particular the processing of personal data. As the new law unfolds an extraterritorial scope, HEIs located outside the European Union (EU) also need to examine whether they are affected, and, if so, take the necessary measures. There is a lack of discussion and approaches in the current literature as to how HEIs can comply with the GDPR regulations. The aim of this study is therefore to analyse scientific publications in order to deliver two results: Firstly, consolidated relevant recommendations and requirements in the context of GDPR, and, secondly, an instrument to help HEIs to raise their GDPR awareness. The latter was built by applying design science guidelines and resulted on a whole of 44 controls that yield a total score. The resulting value can serve as an indicator of HEI's accordance with GDPR regulations. In addition, the compiled controls can be used as a management instrument to assess the measures taken and to continuously promote compliance with GDPR.